Targeting neuropilin-1 interactions is a promising anti-tumor strategy. Issue 5 (5th March 2021) - Liu, Shao-Dan; Zhong, Li-Ping; He, Jian; Zhao, Yong-Xiang
Abstract : Abstract: Neuropilins (NRP1 and NRP2) are multifunctional receptor proteins that are involved in nerve, blood vessel, and tumor development. NRP1 was first found to be expressed in neurons, but subsequent studies have demonstrated its surface expression in cells from the endothelium and lymph nodes. NRP1 has been demonstrated to be involved in the occurrence and development of a variety of cancers. NRP1 interacts with various cytokines, such as vascular endothelial growth factor family and its receptor and transforming growth factor β1 and its receptor, to affect tumor angiogenesis, tumor proliferation, and migration. In addition, NRP1 + regulatory T cells (Tregs) play an inhibitory role in tumor immunity. High numbers of NRP1 + Tregs were associated with cancer prognosis. Targeting NRP1 has shown promise, and antagonists against NRP1 have had therapeutic efficacy in preliminary clinical studies. NRP1 treatment modalities using nanomaterials, targeted drugs, oncolytic viruses, and radio-chemotherapy have gradually been developed. Hence, we reviewed the use of NRP1 in the context of tumorigenesis, progression, and treatment.